Legal Analysis of Cohabitation As a Complaint Offense in the National Criminal Code - Ilmi, Musfiratul; Jannah, Miftahul; Rahman, Mujibur (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to analyze the inclusion of cohabitation in the National Criminal Code (KUHP Nasional). The research method used is normative research which uses secondary data, such as legal rules, norms and expert opinions, as well as using a historical approach. This research does not only look at the reasons for including cohabitation but also discusses the regulation of cohabitation as a complaint offense delict (klacht delict). This research produces an important point that cohabitation is not something new in Indonesia but, long before it was regulated in the National Criminal Code, several regional regulations had previously regulated cohabitation. Apart from that, cohabitation is regulated in a limitative manner, that is, for people who are married, only the husband or wife can complain, and for those who are not married, only parents or children can complain, in this case cohabitation is a complaint offense delict. Thus, there needs to be a unified perception between Law Enforcement Officials including the police, so that in the future there will be no more random raids and the interests of each individual can be protected.